Offshore Renewable Energy: Ocean Waves, Tides and Offshore Wind - Vengatesan Venugopal (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book covers technical articles based on individual contributions from a number of authors working on offshore wind, wave and tidal energy research. Articles describing various aspects of offshore wind, wave and tidal energies including resource prediction, shape optimisation of energy converters, optimal design of rotors for cost reductions, numerical modelling of large scale array energy converters, numerical simulation of electricity converting machines, hybrid energy converters, control system for generators, farm interactions, assessing economic benefits, and energy production benefits have been included in this book. This book will find its use to researchers and industries working in offshore renewable technologies.